HOME BLOOD PRESSURE VARIABILITY AND PRECLINICAL TARGET-ORGAN DAMAGE IN UNTREATED HYPERTENSION. (June 2018) - Kollias, A.; Kyriakoulis, K.; Karpettas, N.; Agaliotis, G.; Geladari, C.; Andreadis, E.; Stergiou, G.S.
Abstract : Objective: To assess the relationship between different indices of home blood pressure (HBP) variability with preclinical target-organ damage in untreated hypertensives. Design and method: Untreated hypertensives were subjected to HBP monitoring (duplicate morning and evening measurements; 6–7 days; automated devices), as well as to assessment of echocardiographic left ventricular mass index (LVMI) and urine albumin excretion (UAE). Results: A total of 276 subjects (mean age 51.8 ± 11 [SD] years, men 58%, body mass index [BMI] 29 ± 4.8 [SD] kg/m 2, HBP systolic/diastolic 139.9 ± 13.1/88.7 ± 8.6 mmHg) were analyzed. Average HBP was correlated to LVMI (n = 263; r = 0.37/0.15, systolic/diastolic, p < 0.01/ < 0.05 respectively) and UAE (n = 230; r = 0.31/0.21, p < 0.01 for both). Maximum systolic HBP was associated with LVMI (r = 0.34, p < 0.01) and UAE (r = 0.31, p < 0.01). Other indices of systolic or diastolic HBP variability (standard deviation, coefficient of variation, average real variability, variability independent of the mean) did not present significant associations with LVMI or UAE (r range from − 0.04 to 0.13, all p = NS). In stepwise multivariate regression analyses (age, gender, BMI, systolic/diastolic HBP, maximum systolic HBP as independent variables), LVMI was determined (R 2  = 0.40) by systolic HBP and age, whereas UAE (R 2  = 0.36) by maximum systolic HBP and male gender. Conclusions: These data suggest that average HBP and maximum systolic HBP, but no other HBP variability indices, appear to determine preclinical target-organ damage in untreated hypertensives.